2017
DOI: 10.3329/bccj.v5i1.32539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical & Microbiological profile of Fournier’s Gangrene in a Tertiary Care Hospital in Bangladesh : A prospective observational study

Abstract: Background: Fournier’s gangrene is the necrotising fasciitis of the genitalia and perineum, with associated poly microbial infection. Evidence based data in the very recent years suggest that it is associated with significant and potential risk of organ failure or death.Aim: This study was designed to be conducted among the patients suffering from Fournier’s gangrene with a view to assess the probable prevalence rate of potentially adverse clinical consequences during course of treatment, overall mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The study done in south Africa, similarly reported the mean hospital length of stay (LoS) being 26 days, overall mortality rate was 11.4% and 13.6% patients were identified as requiring ICU admission based on the need for organ support [23]. However, the review of studies reveals that there is improvement in management of Fournier's gangrene due to recorded reduced mortality from studies done in past two decades like that of turkey with mortality of 40% [24] and others done in India reported the mortality of more than 24% [4] compared to the current study with mortality of 16% and that of Northern Tanzania with mortality of 17% [6].…”
Section: Treatments Modalities and Early Outcomes Of Patients With Fo...mentioning
confidence: 81%
See 3 more Smart Citations
“…The study done in south Africa, similarly reported the mean hospital length of stay (LoS) being 26 days, overall mortality rate was 11.4% and 13.6% patients were identified as requiring ICU admission based on the need for organ support [23]. However, the review of studies reveals that there is improvement in management of Fournier's gangrene due to recorded reduced mortality from studies done in past two decades like that of turkey with mortality of 40% [24] and others done in India reported the mortality of more than 24% [4] compared to the current study with mortality of 16% and that of Northern Tanzania with mortality of 17% [6].…”
Section: Treatments Modalities and Early Outcomes Of Patients With Fo...mentioning
confidence: 81%
“…Founded by jean alfred Fournier's hence the name. The most common isolates are Escherichia coli, Staphylococcus aureus, Saphylococcus pyogenes, Enterococci species and pseudomonas species with E. coli reported to be commonest isolated organism [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations